Salvia beltraniorum (Lamiaceae), a new species in savannoid vegetation from Cosalá, Sinaloa, Mexico - González-Gallegos, Jesús Guadalupe; Pío-León, Juan Fernando; Castro-Castro, Arturo (Phytotaxa, 2021)
An undescribed Salvia species was discovered in savannoid vegetation in the municipality of Cosalá, Sinaloa, during botanical explorations addressed to document the endemic species of this Mexican state. This plant is morphologically most similar to Salvia pringlei, sharing with this the peculiar character of connivent calyces during fructification enclosing the mericarps. However, the new species differs by having smaller floral bracts, deep blue corollas instead of magenta, shorter corollas, corolla lips subequal in length, and shorter connectives and styles. Consequently, we describe and diagnosed this taxon as Salvia beltraniorum. A distribution map, photographs and an identification key to Salvia species in Sinaloa are also provided.